Katalog der in den Sammlungen des Deutschen Entomologischen Institutes aufbewahrten Typen - I (Ephemeroptera, Odonata, Plecoptera). - Petersen, Günther; Gaedike, Hannelore (Contributions to Entomology = Beiträge zur Entomologie, 1968)
The first part of a catalogue for all the types of the collections of the German Entomological Institute (Eberswalde) consists Ephemeroptera, Odonata and Plecoptera.Nomenclatural Actsselenion Ris, 1916 (Agriocnemis), Lectotypeperegrinus Ris, 1916 (Lestes gracilis), Lectotype